2008
DOI: 10.1002/arch.20265
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo effects of myo‐active peptides on larvae of the tomato moth Lacanobia oleracea and the cotton leaf worm Spodoptera littoralis (Lepidoptera; Noctuidae)

Abstract: Neuropeptides from five different neuropeptide families [Manduca sexta allatostatin (Manse-AS), and Manse-AS deletion analogue(5-15), M. sexta allatotropin (Manse-AT), leucomyosuppressin, perisulfakinin, and myoinhibitory peptide I (MIP I)] were assayed for their ability to affect the development and food consumption of penultimate and last larval instars of two lepidopteran species, L. oleracea and S. littoralis. Injections of Manse-AS deletion analogue(5-15), Manse-AT, perisulfakinin, and MIP I had no observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…Interestingly, in almost all other Lepidoptera larvae an in vitro contraction of the foregut is seen. However, in S. littoralis (Matthews et al, 2008) and S. frugiperda (current study), foregut motility is not observed. Therefore, in the current study the ilium was employed to assay myoactivity.…”
Section: Discussioncontrasting
confidence: 75%
“…Interestingly, in almost all other Lepidoptera larvae an in vitro contraction of the foregut is seen. However, in S. littoralis (Matthews et al, 2008) and S. frugiperda (current study), foregut motility is not observed. Therefore, in the current study the ilium was employed to assay myoactivity.…”
Section: Discussioncontrasting
confidence: 75%
“…In particular, the ASTs have been shown to inhibit contractions of visceral muscle including the foregut and hindgut (Lange et al, 1993;Sarkar et al, 2003;Predel et al, 2001;Matthews et al, 2008), and have been localized to endocrine cells of the gut (Veenstra et al, 1995;Veenstra, 2009;Reichwald et al, 1994;Robertson and Lange, 2010), suggesting that they may have a role in feeding and digestion. In the cockroach, ASTs have been shown to decrease food consumption (Aguilar et al, 2003).…”
Section: Research Articlementioning
confidence: 99%
“…([M1H] contractions in the foregut of larval Lepidoptera are inhibited by Manse-AS (Duve et al, 2000;Audsley et al, 2001;Matthews et al, 2006Matthews et al, , 2007, and injection of Manse-AS into Lacanobia oleracea L. and Spodoptera littoralis (Boisduval) larvae reduced feeding, growth, and survival. It was proposed that the effects of Manse-AS in vivo were probably due to the inhibitory actions of the peptide on foregut peristalsis, preventing the movement of food through the alimentary canal, resulting in suppression of feeding activity (Matthews et al, 2008). It is possible that both Manse-AS and dR 3 dR 5 Manse-AS act in a similar manner when fed to aphids.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the ability of Manse-AS to adversely affect lepidopteran and aphid pest species, its potential as an insect control agent may be hindered because of its susceptibility to gut enzymes. Although Manse-AS is active when fed to aphids, feeding this peptide to larvae of L. oleracea had no effect, most likely due to degradation by digestive enzymes Effects of Manse-AS and an Analogue on M. persicae in the foregut (Matthews et al, 2008). Foregut extract from L. oleracea has been shown to rapidly degrade Manse-AS, with a half-life of approximately 5 min (Audsley et al, 2002a).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation